Reference Gene Selection for Normalizing Gene Expression in Ips Sexdentatus (Coleoptera: Curculionidae: Scolytinae) Under Different Experimental Conditions - Sellamuthu, Gothandapani; Amin, Shan; Bílý, Jan; Synek, Jirí; Modlinger, Roman; Sen, Madhab Kumar; Chakraborty, Amrita; Roy, Amit (Frontiers in Physiology, 2021)
Ips sexdentatus (Coleoptera: Curculionidae: Scolytinae) is one of the most destructive and economically important forest pests. A better understanding of molecular mechanisms underlying its adaptation to toxic host compounds may unleash the potential for future management of this pest. Gene expression studies can be considered one of the key experimental approaches for such purposes. A suitable reference gene selection is fundamental for quantitative gene expression analysis and functional genomics studies in I. sexdentatus. Twelve commonly used reference genes in Coleopterans were screened under different experimental conditions to obtain accurate and reliable normalization of gene expression data. The majority of the twelve reference genes showed a relatively stable expression pattern among developmental stages, tissue-specific and sex-specific stages; however, some variability was observed during varied temperature incubation. Under developmental conditions, Tubulin beta-1 chain (β-Tubulin) was the most stable reference gene, followed by translation elongation factor (eEF2) and ribosomal protein S3 (RPS3). In sex-specific conditions, RPS3, β-Tubulin, and eEF2 were the most stable reference genes. In contrast, different sets of genes were shown higher stability in terms of expression under tissue-specific conditions, i.e., RPS3 and eEF2 in head tissue, V-ATPase-A and eEF2 in fat body, V-ATPase-A and eEF2 in the gut. Under varied temperatures, β-Tubulin and V-ATPase-A were most stable, whereas ubiquitin (UbiQ) and V-ATPase-A displayed the highest expression stability after Juvenile Hormone III treatment. The findings were validated further using RT-qPCR based target gene expression analysis. Nevertheless, the present study delivers a catalogue of reference genes under varied experimental conditions for the coleopteran forest pest I. sexdentatus and paves the way for future gene expression and functional genomic studies on this species.